Novel isolated, L‐amino acid‐ligated rhodium catalysts that induce highly helix‐sense‐selective polymerization of an achiral 3, 4, 5‐trisubstituted phenylacetylene. Issue 15 (24th March 2016) - Jia, Hongge; Shi, Yongqiang; Ma, Liqun; Gao, Xuan; Wang, Yazhen; Zang, Yu; Peng, Jijun; Aoki, Toshiki; Teraguchi, Masahiro; Kaneko, Takashi; Masuda, Toshio
ABSTRACT: Two novel chiral well‐defined rhodium complexes, Rh(cod)(L‐Phe) (cod = 1, 5‐cyclooctadiene, Phe = phenylalanine) and Rh(cod)(L‐Val) (Val = valine) were synthesized, isolated by recrystallization, and characterized. The helix‐sense‐selective polymerization (HSSP) of an achiral 3, 4, 5‐trisubstituted phenylacetylene, p ‐dodecyloxy‐ m, m ‐dihydroxyphenylacetylene (DoDHPA) was examined by using the two Rh complexes as catalysts. These catalysts provided high molecular weight polymers ( M w 28 × 10 4 −45 × 10 4 ) in about 40%–85% yields. The resulting polymers exhibited a bisignated CD signal at about 300 nm and a broad signal around 470 nm, indicating that they have preferential one‐handed helical structure. The present catalysts achieved larger molar ellipticity up to [ θ ]310 = 13.0 × 10 4 deg cm 2 /dmol than those with binary chiral catalytic systems, [Rh(cod)Cl]2 /(L‐phenylalaninol), [Rh(cod)Cl]2 /(L‐valinol), and [Rh(nbd)Cl]2 /(R)‐PEA. All these results manifest that the present, well‐defined Rh complexes serve as excellent catalysts for the HSSP of DoDHPA. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2346–2351 Abstract : The novel Rh(cod)(L‐phenylalanine) and Rh(cod)(L‐valine) (cod = 1, 5‐cyclooctadiene) catalysts were synthesized and isolated for the first time. The HSSP of an achiral 3, 4, 5‐trisubstituted phenylacetylene, p ‐dodecyloxy‐ m, m‐ dihydroxyphenylacetylene (DoDHPA) was performed by these catalysts to provide polymers with high molecular weights and [ θ ] values in high yields. The novel catalysts could induce the helix structure of polymer more efficiently than binary catalysts.